Special Characteristics of Accounting in Slovenian Social Enterprises - Andreja Lutar Skerbinjek (Naše gospodarstvo/Our economy, 2013)
Social enterprise is new type of enterprise established under the Social Entrepreneurship Act. According to this act, it is not necessary for an enterprise to perform only social activities; it can perform other activities as well. Thus, it is necessary to record costs, revenues, and expenses separately for social entrepreneurship activities and other activities. Special characteristics are connected with assets, liabilities and spe- cial forms of financial statements. In addition to the financial statements, appropriate notes to the financial statements should be included. This paper presents special characteristics of accounting in social enterprises, as defined in the Social Entrepre- neurship Act and Slovene Accounting Standard 40—Accounting solutions in social businesses.